Perancangan Sistem E-Medical Record Dengan Sinyal Auskultasi Berbasis Web - Hezron Eka Lattang; Achmad Rizal; Sofia Naning Hertiana (eProceedings of Engineering, 2015)
Has made an application that aims to develop a telemedicine services in cyberspaces, that is e-medical record application web-based that to be design using PHP programming language and MySQL as database. In this application, not only displays data of patient’s health condition, but also auscultation signals for analyze the patient’s health by docter easily. The system consists of 2 applications, client and server applications. On the client application, the patient input medical record which required for docter to analysis patient’s health into database. On client application, docter analyze patient’s medical record and send it to patient account as patient’s medical history. There are some stages for design this system, starting from design web and database and also testing functional of web. The result is an application of e-medical record web-based with auscultation signal. This system capable to do input, send, and save patient’s medical record as patient’s medical history. By this system is expected to be more effective and efficient for health services, and can improve qualityof care and clinical workflow. Keywords: web, e-medical record, auscultation signals, telemedicine, PHP, MySQL